2019
DOI: 10.3390/ani9090651
|View full text |Cite
|
Sign up to set email alerts
|

One Iron Injection Is Not Enough—Iron Status and Growth of Suckling Piglets on an Organic Farm

Abstract: Simple SummarySuckling piglets need more iron for rapid and healthy growth than is available from sow’s milk alone. Therefore, iron supplementation is common on both conventional and organic farms and is usually carried out by a single injection of 200 mg iron during the piglets’ first days of life. However, the long suckling periods in organic pig farming can still lead to iron deficiency, as we found in a study with 288 piglets on an experimental farm. A single subcutaneous injection of iron led to lower iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
10
2
Order By: Relevance
“…This indicates that the piglets could not meet their daily iron requirement over the suckling period and need an iron injection at birth. Furthermore, daily gain during suckling period increased from the first week to weaning [ 21 ] and hemoglobin and hematocrit decreased from d 17 to 21 of age after the iron injection at birth [ 6 , 17 ]. This supports the suggestion that an additional iron injection may be needed when they are weaned at older age over d 21 of age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that the piglets could not meet their daily iron requirement over the suckling period and need an iron injection at birth. Furthermore, daily gain during suckling period increased from the first week to weaning [ 21 ] and hemoglobin and hematocrit decreased from d 17 to 21 of age after the iron injection at birth [ 6 , 17 ]. This supports the suggestion that an additional iron injection may be needed when they are weaned at older age over d 21 of age.…”
Section: Discussionmentioning
confidence: 99%
“…However, Friendship et al [ 3 ] reported that a single iron injection at d 4 of age was not sufficient to prevent iron deficiency at weaning ranged from 16 to 21 d. Perri et al [ 4 ] also reported that the traditional 200 mg of iron injection is insufficient to meet the needs for iron for the large and fast-growing piglets. As piglets grow fast during the suckling period and weaning weight increases with increasing weaning age up to d 28 of age, a single iron injection at birth may not be sufficient to prevent large piglets from anemia at weaning, which may result in growth retardation afterward [ 5 , 6 , 7 ]. However, Williams et al [ 8 ] reported that intramuscular injection of a 200 mg iron within 7 d after birth was sufficient to optimize pre- and postweaning growth performance of pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that supplemented piglets born outdoors had higher haemoglobinemia and body weight at weaning and lower pre-weaning morbidity and mortality than unsupplemented pigs [175]. Finally, a more recent study showed that a second iron intake at about 2 weeks of age can even be useful in organic piglets weaned at about 42 (±1.7) days of age, to ensure adequate iron intake and better piglet growth until weaning [176]. It is therefore probably appropriate to assume that the risk of anaemia is low in free-range farms where the soil provides iron in its intrinsic composition [41].…”
Section: Anaemia and Iron Supplementationmentioning
confidence: 99%
“…Parenteral iron administration prevents iron deficiency anaemia, a condition which can reduce growth rates and increase disease susceptibility and mortality [4]. A single dose of iron may not provide sufficient iron for adequate growth, suggesting a requirement for multiple post-natum injections, particularly on organic farms where piglets experience extended suckling periods [5].…”
Section: Introductionmentioning
confidence: 99%